2019
DOI: 10.1101/736793
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of 20 enset (Ensete ventricosum) landraces for response to Xanthomonas vasicola pv. musacearum infection

Abstract: Bacterial wilt, caused by Xanthomonas vasicola pv. musacearum (Xvm), formerly X. campestris pv. musacearum, is the most threatening and economically important disease of enset (Ensete ventricosum), the multipurpose food security crop orphan to south and southwestern Ethiopia. Xvm has also had a major impact on banana and plantain production in East Africa following its detection in Uganda in 2001 and subsequent spread. Effective control of this disease currently relies on integrated disease management (IDM) st… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
(1 reference statement)
0
3
0
Order By: Relevance
“…For example, three landraces of Ensete among 20 studied were found to be resistant to Xanthomonas vasicola pv. musacearum (Muzemil et al, 2019). A similar study from 72 diverse Musa cultivars identified several resistant genotypes, mostly with BB or hybrid AB genome types (Nakato et al, 2019).…”
Section: Resultsmentioning
confidence: 78%
“…For example, three landraces of Ensete among 20 studied were found to be resistant to Xanthomonas vasicola pv. musacearum (Muzemil et al, 2019). A similar study from 72 diverse Musa cultivars identified several resistant genotypes, mostly with BB or hybrid AB genome types (Nakato et al, 2019).…”
Section: Resultsmentioning
confidence: 78%
“…musacearum), whilst 'Gefetanuwa', which supported the highest reproduction of P. goodeyi, also supports rapid X. vasicola pv. musacearum development, as does 'Arkiya', which has been used as a susceptible control in evaluation studies (Muzemil et al, 2019). Although 'Arkiya' was regarded as one of the cultivars with higher densities of P. goodeyi in a previous survey (Bogale et al, 2004), the P f and RF were similar to the other two cultivars ('Maziya' and 'Heila').…”
Section: Discussionmentioning
confidence: 97%
“…This suggests a predominantly genetic (rather than agronomic or environmental) basis to farmer-selected attributes and enables initial future characterization of poorly known landraces based on genotype (Borrell et al, 2021). In addition, evidence of a genetic basis for traits such as disease tolerance enable easier comparison of extensive regional Ethiopian literature that has assessed disease response in limited numbers of landraces (Gezahegn & Mekbib, 2016;Haile et al, 2020;Muzemil et al, 2021). This also highlights the challenge of trait analysis using only vernacular information.…”
Section: Vernacular Genetic and Trait Diversitymentioning
confidence: 99%